Rediseño interiorista integral de la casa patrimonial de la familia Cifuentes Terán en galería de arte - Gastro Bar - Quito - Solórzano Rosales, Pablo Andrés (2017)
The deficiency of spaces of cultural appreciation in the city is a problem that today the exponents of the art seek to solve, inquiring to expose their works in spaces that are destined for this activity. These spaces need optimum lighting and spatial dynamics for their interpretation and visualization. Before this event it is proposed to approach the subject locating a proposal that facilitates exhibition spaces integrating with a restaurant offering a complementary space. Coupled with the essence of two different typologies will provide a space aimed at maintaining functionality, harmony and comfort for its users.